Field margins: a comparison of establishment methods and effects on hymenopteran parasitoid communities. Issue 4 (6th September 2013) - Ó hUallacháin, Daire; Anderson, Annette; Fritch, Rochelle; McCormack, Stephen; Sheridan, Helen; Finn, John A.; Stewart, Alan; Quicke, Donald
Abstract Field margins within intensively managed ecosystems are often seen as a last refuge for biodiversity, and are typically targeted with measures within many agri‐environment schemes. Grassland accounts for 81 million ha of land within the EU; however, the ecology of field margins associated with permanent grassland has not been well studied. This study investigated the effects of experimental field margin measures on hymenopteran parasitoid communities over a 5‐year period. Hymenopteran parasitoids were chosen because they occupy high trophic levels, feed on a diverse range of plant and invertebrate hosts, and are considered good indicators of arthropod diversity. Establishment methods included: fencing, natural regeneration, and reseeding with a wildflower mixture, at three margin widths. Field margin establishment method had a significant effect on abundance of parasitoids. Establishment method did not have a significant effect on parasitoid genera diversity, but did affect parasitoid community composition. Margin width had no significant impact on parasitoid communities. Grazing had a significant negative effect on parasitoid genus richness and community structure. This suggests that structural diversity of vegetation plays an important role in parasitoid community structure. Plant species richness did not significantly affect parasitoid abundance or genera richness. Noxious species within plots resulted in a significantly greater abundance and diversity of parasitoids and of idiobionts in particular. Where plant species richness is limited, simple measures such as fencing of narrow field margins may be as effective at increasing parasitoid taxon richness and abundance (indicators of arthropod richness and abundance) as expensive measures such as reseeding and wider margin widths.